Considerations for implementing source separation and treatment of urine, graywater, and blackwater - Fewless, Kimberly LeMonde, author; Sharvelle, Sybil, advisor; Bledsoe, Brian, committee member; Goemans, Chris, committee member (Colorado State University. Libraries, 2015)
Source separation integrated with decentralized wastewater treatment offers the possibility of recovering nutrients, reducing release of micropollutants to the environment, and increasing water recycling more efficiently than centralized wastewater treatment. Nutrient effluent discharge limits and guidelines for wastewater treatment plants are becoming stricter, and nutrient removal or recovery is very costly for the large volumes present. This is driving innovation in wastewater treatment. Three waste streams are identified for potential source separation and treatment: urine, graywater (non-kitchen sinks, showers/bath, and laundry), and blackwater (feces and kitchen wastewater). Urine is only 1% of the domestic wastewater stream, but contains 50-80% of the nutrients (nitrogen, phosphorus, and potassium) and the majority of pharmaceuticals and hormones. Blackwater has high organic and nutrient content, solids, and pathogens, and carries the remaining pharmaceutical/hormone residues. Graywater is the largest contributor to total volume but is the least contaminated of the three streams (low in nutrients and pathogens, but contains detergents and personal care products). In the absence of kitchen wastewater, graywater is also low in organic content. If these streams are separated at the source, maximum reuse of water can be achieved with minimal treatment (e.g. graywater). More importantly, avoiding dilution of nutrients and pharmaceuticals/hormones allows for more advanced treatment without excess cost. A literature review led to the conclusion that the best options for urine treatment are struvite precipitation for phosphorus recovery and ammonia stripping for nitrogen recovery. Anaerobic digestion is ideal for blackwater and constructed wetlands can be used for graywater treatment. A neighborhood system of 500-1000 homes with decentralized treatment of urine, graywater, and blackwater is proposed. Almost complete recovery of nutrients could be achieved from urine, graywater could be treated and “locally” recycled, and energy and nutrients could be recovered from blackwater. A wastewater treatment system combining these components has not yet been tested in a pilot project; however, the individual treatment systems have been operated in pilot projects (or at larger scales) with similar waste streams. Modification of regulatory framework will be necessary to accommodate water reuse and effluent regulations at the proposed decentralized scale. Although nutrient reuse is a goal in the proposed system, farmer and consumer acceptance in the U.S. are unknown, but critical. Technical obstacles to implementation include improving urine diversion toilets and treatment systems (primarily decreasing maintenance and increasing automation), managing urine scale (spontaneous precipitation in pipes), avoiding or capturing volatilized ammonia in urine transport, and better characterizing waste streams for treatment optimization. Research and development should focus on decreasing maintenance of urine diversion components and increasing automation. It is also necessary to better define influent quality and effluent goals and to optimize treatment systems for the proposed configuration. The waste stream produced from urine treatment also needs consideration, as it is likely to by highly concentrated with pharmaceuticals. A pilot project in the U.S. is recommended to resolve technical issues. A preliminary review of costs reveals that, as is typically the case with new technologies, urine diversion toilets and struvite precipitation reactors have high investment and operational costs. Despite this, early estimates indicate that urine diversion systems are less costly than adding nutrient removal in wastewater treatment plants. In addition, the high costs of urine diversion systems are largely due to maintenance requirements and economies of scale (aspects that will change with research and development). In moving forward, it will be beneficial to conduct an economic analysis of greater breadth, with consideration of water reuse, energy use/carbon footprint, cost of fertilizer production, potential revenue of recovered nutrients, and economic externalities. It is also important to consider the reality of transition: that unless conventional wastewater treatment becomes more expensive (due to nutrient regulations) or homeowners are willing to cover the extra cost of a decentralized system with urine diversion, developers/homeowners are likely to choose tapping into the current system. Although technical issues are pressing and infrastructure requirements are extensive for the proposed decentralized system, the technical, social, and regulatory issues are not insurmountable. The potential in improved treatment (nutrient and micropollutant removal), energy generation and increased water recycling suggests moving forward with research and development in the U.S., including a pilot project.
Keywords: graywater; urine treatment; blackwater; wastewater treatment; source separation